SPECIFIC ASPECTS OF THE INFLUENCE OF PSYCHO-EMOTIONAL STATES ON THE PROFESSIONAL ACTIVITY OF ACADEMIC STAFF (Eureka Journal of Education & Learning Technologies, 2026)
Improving the quality and effectiveness of higher education worldwide, strengthening collaboration between students and academic staff within the educational process, and ensuring successful employment opportunities for university graduates have become priority areas in contemporary educational development1. In this regard, experiences of countries with highly developed educational systems demonstrate that the indicators and dynamics of scientific creativity create favorable conditions for strengthening professionally significant qualities among academic staff. This tendency highlights the necessity of identifying psychological factors that effectively influence the professional development of academic personnel and conducting scientific investigations into the impact of psycho-emotional states on pedagogical behavior.